Hubungan Pengetahuan Tentang Virus Dan Kepatuhan Prokes 5-M Siswa - Riyanti, Hurip Budi; Sulistyaningsih , Endang (Universitas Negeri Surabaya, 2022)
In the verse of Yaseen 36 it is written that there is something unknwon to people at the time. Today we know there is supermicroorganism - that is virus. Virus is the cause of some infection like what happened since early 2020 when the pandemy occurred. The virus is beta-coronavirus novel. This is the new type of corona. It is the cause of Coronavirus Disease 2019 (Covid-19). Some efforts to overcome the disease includes health protocol such as 5 M in Bahasa Indonesia (wearing mask, washing hands, physical distancing, avoiding crowd, and limiting mobility). Implementation of the health protocol is limited when the public does not support. Public compliance to the policy is influenced by several factors like age and education. The objective of the research is to find out the corelation betweeen knowledge about Covid-19 with compliance to health protocol (5M). I use methodes of survey by filling out questionnaire to students of SMP Islam Al Aszar 10, Kembangan, Jakarta. The result is calculated by using linier equation between knowledge and compliance. Intercept (a)= 60,34641; slope (b)= 0,358306 and corelation (r)= 0,949393. X is knowledge and Y is complaince. From the research we come to a conlusion that some knowledge is still lacking like the life of virus, prevention of cantagion, the size of virus and covid-19. But they comply woth the health protocol of 5 M, seen from slope 0,358306. Although knwledge (X) is low , Y (compliance) high almost the same . It is because the government, the school and the researcher have given some informations about the importance of health protocol of 3 M and now 5 M.